Regional differences in the incidence of self-reported type 2 diabetes in Germany: results from five population-based studies in Germany (DIAB-CORE Consortium) - Schipf, Sabine; Ittermann, Till; Tamayo, Teresa; Holle, Rolf; Schunk, Michaela; Maier, Werner; Meisinger, Christine; Thorand, Barbara; Kluttig, Alexander; Greiser, Karin Halina; Berger, Klaus; Müller, Grit; et al. (Journal of epidemiology and community health, 2014)
Cohort studies; Epidemiological methods; Epidemiology of diabetes; GEOGRAPHY